2019
DOI: 10.1097/md.0000000000017412
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of long non-coding RNA CCAT2 predicts poorer prognosis in patients with hepatocellular carcinoma

Abstract: Background:Long non-coding RNA colon cancer-associated transcript 2 (CCAT2) is a 1752-bp lncRNA transcribed from m8q24 genomic region. A lot of investigations have confirmed the involvement of CCAT2 in the tumorigenesis of many cancer types. Previous studies found that over-expression of CCAT2 significantly promoted cell migration and proliferation, and inhibited apoptosis of HCC cells. In the present investigation, the clinical value and prognostic significance of CCAT2 were investigated.Methods:The 122 pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…[11][12][13] Recent studies have shown that lncRNA regulates cell proliferation, apoptosis, metastasis, invasion, angiogenesis, lipid metabolism, EMT, and many other processes, and has an impact on tumor size, TNM grade, postoperative survival, and prognosis of HCC. 8,[14][15][16] Bioinformatics analysis and luciferase reporter assay found that the binding site of SNHG11 is miR-184 and miR-184 directly targets AGO2. In this study, SNHG11 downregulated the expression of miR-184 and upregulated AGO2 expression, and thereby regulated cell viability, invasion, migration, and promoted apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Recent studies have shown that lncRNA regulates cell proliferation, apoptosis, metastasis, invasion, angiogenesis, lipid metabolism, EMT, and many other processes, and has an impact on tumor size, TNM grade, postoperative survival, and prognosis of HCC. 8,[14][15][16] Bioinformatics analysis and luciferase reporter assay found that the binding site of SNHG11 is miR-184 and miR-184 directly targets AGO2. In this study, SNHG11 downregulated the expression of miR-184 and upregulated AGO2 expression, and thereby regulated cell viability, invasion, migration, and promoted apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…rs6983267 resides in the intronic region of POU5F1B, which encodes a transcriptional activator implicated in multisite cancers (48)(49)(50)(51). It is worth noting that this genetic variant is also localized inside the CCAT2 lncRNA upregulated in colon cancer and implicated in other human malignancies (52)(53)(54)(55). The exact roles of either POU5F1B or CCAT2 in PTC remain to be established.…”
Section: Discussionmentioning
confidence: 99%
“…CCAT2 is 1,752 bp in length and is located within the chromosome 8q24.21 gene desert adjacent to Myc ( 201 ). Amplification of the oncogenes in the 8q24.21 region has been found in numerous human cancers.…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%